(untitled) (Journal of Applied Learning and Teaching, 2020)
At present, Western universities are undergoing structural and institutional change in response to the growing demands to provide additional online course and degree options, improve the recruitment, retention and support of Indigenous students, and undergo Indigenisation (of governance, the offered curricula, its faculty and campuses). In Australia, there have been increasing efforts to Indigenise curricula within law, humanities and the social sciences; prompting the formulation and execution of innovative pedagogical practices and online content. Efforts to harmonise these two emerging educational “frontiers” have been tried, one innovative measure trialled is the concept of virtual touring of Country alongside Indigenous Elders and knowledge holders, bringing together Indigenous epistemes and place-based learning. In analysing student unit evaluations, results indicate that students found the virtual tours of Country to be the most effective and meaningful aspect of the unit overall. We argue this demonstrates that what we call “digital placebased learning” is a useful method to engage undergraduate students in Indigenous epistemologies and ontologies, whilst offering a unique experience across three regions.